ウミタカマル ニヨル ソクシン ケッカ ニツイテ - 小沢, 敬次郎; オザワ, ケイジロウ; 柳川, 三郎; ヤナガワ, サブロウ; 磯打, 勉; イソウチ, ツトム; 小竹, 勇; コタケ, イサム; OZAWA, Keijiro; YANAGAWA, Saburo; ISOUCHI, Tsutomu; KOTAKE, Isamu (国立極地研究所, 1963)
P(論文) During the cruise of the "UMITAKA-MARU" in the Antarctic, the far southern Indian and Atlantic Ocean, the depths surveys were carried out from Fremantle, Western Australia to Cape Town via South Georgia. This was the continuation of the survey in the previous cruise between December 1956 and March 1957. Prior to this cruise, the synchronous oscillating equipment for the source of driving motor was newly built in the deep-sea type echo-sounding machine, accordingly the regulation of the recorder was remarkably improved. Obtained depths were corrected with draft and applied corrections of sound velocity in the water at fields, actually the correction curves showing in Fig. 2 were fixed on measured depths. These sounding data were newly entered in the bathymetric charts, which were published at first on March 1, 1954 from the International Hydrographic Bureau and in which obtained depths on the previous cruise have been added (Fig. 10). Depending on sounding data and continuous recording, profiles of the bottom along the ship's track were drawn. Fig. 3 shows a profile from Fremantle to the northern edge of pack ice surrounding Antarctica, showing the track in Fig. 2, and profiles of South. Indian rise and Kerguelen-Gaussberg rise on the route were drawn in detail in Fig. 4 and the under-part of Fig. 5. Fig. 7 shows a profile from Lat. 59° S, Long. 12°27' E to Agulhas bank of South Africa, the detailed profile crossing Atlantic-Indian rise is shown in Fig. 8. The local bathymetric charts of Kerguelen-Gaussberg rise and in the western vicinity of Clerke Rock which lies in south-east of South Georgia, are shown in Figs. 5 and 6. Rises occurring along the ship's track, the South Indian rise and Atlantic-Indian rise, except the Kerguelen-Gaussberg rise being smooth shaped with a crack on the top, are rugged ones and rising towards the middle, where rift valley occurs, these show similarity of other ridges and rises throughout the world as mentioned by BRUCE C. HEEZEN. This particularity was distinguishly ...